Ekologisk nötköttsproduktion i Gävleborgs län - Rangrost, Johanna (SLU/Dept. of Animal Environment and Health (until 231231), 2004)
The objective of this study was to make an inventory and a potential analysis of the organic beef production in the region of Gävleborg, Sweden. A survey was conducted, where a questionaire was sent to all farmers in the region who had environmental subsidies concerning organic cropping systems in 2001. In total, there were 701 farmers, of which 46 % participated in the study. Three slaughter houses were interviewed to get their pictures of the development of organic beef production. The study shows that there are potentials and interests in the region to increase the production of organic beef. Cattle on farms with organic cropping systems constitute 18 % of the total number of cattle in the region. However, in the study only 42 % of the farms with organic cropping systems have cattle reared organicly according to EU rules for organic animal production. Furthermore, only 18 % of the farms with organic cropping systems are associated to KRAV (the organic certification organisation). The cost for certifying production according to KRAV is high if the production is small. Several of the farmers in the study would have certified their production according to KRAV if the certification was less expensive, as many farms have too small of a production to get a certification profitable. Another problem for an increased production of organic beef in the region is the lack of demand. Slaughter houses and food industry cannot sell all the organic beef that can be produced. Local operators could give the organic beef a positive development. Product development, exposure and marketing of the products are necessary to give the consumers possibilities to explore and choose organic beef.